Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
1, 54 : x - 1 = 5
54 : x = 5+1 = 6
x = 54 : 6 = 9
2, 42 : x + 0 = 8
x = 42 : 8 = 21/4
3, 24 : x - 8 = 0
24 : x = 0 + 8 = 8
x = 24 : 8 = 3
Tk mk nha
x+4/7=3/4 x-3/4=2/5 x x 2/3=3/4x1/2
x=3/4-4/7 x=2/5+3/4 x x2/3=3/8
x=21/28-16/28 x=8/20+15/20 x=3/8:2/3
x=5/28 x=23/20 x=9/16
1. Đề:...........
<=> x = 3/4 - 4/7
<=> x = 5/28
Vậy x = 5/28
2. Đề:............
<=> x = 2/5 + 3/4
<=> x = 23/20
Vậy x = 23/20
3. Đề:..........
<=> x. 2/3 = 3/8
<=> x = 3/8. 3/2
<=> x = 9/16
Vậy x = 9/16
1. 41/7 - x = 25/9
=> x = 41/7 - 25/9
=> x = 194/63
2. 3x = 12,8
=> x = 12,8 : 3
=> x = 64/15
3. 41/2 x = 5
=> x = 5: 41/2
=> x = 10/41
4. 3/4 x = 1
=> x = 1: 3/4
=> x = 3/4
5. 4/5 : x = 3
=> x = 4/5 : 3
=> x = 4/15
6. 12/x = 4
=> x = 12/4
=> x = 3
7. 4/7 : x = 4/7
=> x = 4/7 : 4/7
=> x = 1
8. 2x - 3/4 = 7/8
=> 2x = 7/8 + 3/4
=> 2x = 13/8
=> x = 13/8 : 2
=> x =13/16
Ruby Chan :))
1, \(4\frac{1}{7}-x=2\frac{5}{9}\)
\(\frac{4\times7+1}{7}-x=\frac{2\times9+5}{9}\)
\(\frac{29}{7}-x=\frac{23}{9}\)
\(x=\frac{29}{7}-\frac{23}{9}\)
\(x=\frac{261}{63}-\frac{161}{63}\)
\(x=\frac{100}{63}\)
2, \(3\times x=12,18\)
\(x=12,18\div3\)
\(x=4,06\)
3, \(4\frac{1}{2}\times x=5\)
\(\frac{4\times2+1}{2}\times x=5\)
\(\frac{9}{2}\times x=5\)
\(x=5\div\frac{9}{2}\)
\(x=\frac{5\times2}{9}=\frac{10}{9}\)
4, \(\frac{3}{4}\times x=1\)
\(x=1\div\frac{3}{4}\)
\(x=\frac{1\times4}{3}=\frac{4}{3}\)
5, \(\frac{4}{5}\div x=3\)
\(x=\frac{4}{5}\div3\)
\(x=\frac{4}{5\times3}=\frac{4}{15}\)
6,\(\frac{12}{x}=4\)
\(x=12\div4\)
\(x=3\)
7, \(\frac{4}{7}\div x=\frac{4}{7}\)
\(x=\frac{4}{7}\div\frac{4}{7}\)
\(x=1\)
8, \(2x-\frac{3}{4}=\frac{7}{8}\)
\(2x=\frac{7}{8}+\frac{3}{4}\)
\(2x=\frac{7}{8}+\frac{6}{8}\)
\(2x=\frac{13}{8}\)
\(x=\frac{13}{8}\div2\)
\(x=\frac{13}{8\times2}=\frac{13}{16}\)
2 * x + 14 * (34-9) = 900
2 * x + 14 * 25 = 900
2 * x + 350 = 900
2 * x = 550
x = 550 : 2
x = 275
97 - x =486 : 27
97 - x = 18
x= 97 - 18
x = 79
9 * x - 4 * x = 24 * 5
9 * x - 4 * x = 120
( 9 - 4 ) * x = 120
5 * x =120
x= 120 :5
x =24
dài v ~
4/3 * (7/2 - 5/4 ) - 3/4 * x =2
4/3 * 9/4 - 3/4 * x = 2
3 - 3/4 * x = 2
9/4 * x =2
x = 2 : 9/4
x = 8/9
~~~~~~~~~~
5/3 * x - 3/4 * x + 4/3 = 11/6
( 5/3- 3/4 ) * x + 4/3 =11/6
11/12 * x + 4/3 = 11/6
11/12 * x = 11/6 - 4/3
11/12 * x = 1/2
x= 1/2 : 11/12
x=6/11
dài quá mức bấm mãi ~
Tìm x:
a)
2 * x + 14* ( 34 - 9 ) = 900
2* x + 14 * 25 = 900
2*x + 350 = 900
2*x = 900 - 350
2*x = 550
x = 550 : 2
x = 275
b)
97 - x = 486: 27
97 - x = 18
x = 97 - 18
x = 79
c) 9 * x - 4 * x = 24 * 5
x - ( 9* 4 ) = 120
x - 36 = 120
x = 120 + 36
x = 156
Ủng hộ nha! ^.^
4/7 + x = 2
x = 2 - 4/7
x =10/7
1 3/4 - x = 3/4
x =1 3/4 - 3/4
x = 1
2/3 . (x-1/3)=4/5
x - 1/3 = 4/5 : 2/3
x - 1/3 = 6/5
x = 6/5 + 1/3
x = 23/15
Bài 1:
a; (\(\dfrac{1}{4}\)\(x\) - \(\dfrac{1}{8}\)) x \(\dfrac{3}{4}\) = \(\dfrac{1}{4}\)
\(\dfrac{1}{4}x\) - \(\dfrac{1}{8}\) = \(\dfrac{1}{4}\) : \(\dfrac{3}{4}\)
\(\dfrac{1}{4}\)\(x\) - \(\dfrac{1}{8}\) = \(\dfrac{1}{4}\) x \(\dfrac{4}{3}\)
\(\dfrac{1}{4}x\) - \(\dfrac{1}{8}\) = \(\dfrac{1}{3}\)
\(\dfrac{1}{4}x\) = \(\dfrac{1}{3}\) + \(\dfrac{1}{8}\)
\(\dfrac{1}{4}\) \(x\)= \(\dfrac{8}{24}\) + \(\dfrac{11}{24}\)
\(\dfrac{1}{4}x=\dfrac{11}{24}\)
\(x=\dfrac{11}{24}:\dfrac{1}{4}\)
\(x=\dfrac{11}{24}\times4\)
\(x=\dfrac{11}{6}\)
b; \(\dfrac{12}{5}:x\) = \(\dfrac{14}{3}\) x \(\dfrac{4}{7}\)
\(\dfrac{12}{5}\) : \(x\) = \(\dfrac{8}{3}\)
\(x\) = \(\dfrac{12}{5}\) : \(\dfrac{8}{3}\)
\(x\) = \(\dfrac{12}{5}\) x \(\dfrac{3}{8}\)
\(x\) = \(\dfrac{9}{10}\)
a) x + 1/15 = 1/3 - 1/4 = 4/12 - 3/12 = 1/12.
=> x = 1/12 - 1/15 = 5/60 - 4/60 = 1/60.
b) x - 5/12 = 1/3 + 1/4 = 4/12 + 3/12 = 7/12.
=> x = 7/12 + 5/12 = 1
c) x x 2/7 = 3/4 x 4/15 = 1/5
=> x = 1/5 : 2/7 = 1/5 x 7/2 = 7/10
d) x : 3/8 = 4/3 : 3/6 = 4/3 x 2 = 8/3
=> x = 8/3 x 3/8 = 1
2x4=8
3x4=12
4x4=16
2x4=8
3x4=12
4x4=16